Effectiveness of Geometry Learning Based on PPG Daljab Student Technology through the Project-Based Learning Model in Elementary School Students - Katuuk, Deitje Adolfin; Tarusu, Deysti Trifena (International Journal of Information Technology and Education, 2024)
Difficulties in understanding the mathematical concepts that occur when students learn geometry, one of which is an abstract geometry concept that is not followed by effective learning as an effort to help students' understanding is the main problem in this study. This study aims to determine the effectiveness of technology-based geometry learning carried out by PPG Daljab students through the Project Base Learning model in elementary school students. This study uses a quantitative approach with the type of Quasi-Experimental Design research with the Nonequvalent Control Group Design form. The population in this study is all elementary school fifth students in the North Tomohon Cluster, Tomohon City totaling 62 students. The sampling technique used in this study was Pusposve Sampling which was taken by two schools with the same level of activity and learning achievement. The experimental class was SD Inpres Kakasasen Satu and SD Inpres Kayawu with 31 students, while the control class was SD Inpres Kakasasen Dua and SD Inpres Kakasasen Tiga with 31 students. Data collection techniques using the Geometry Understanding Test Instrument. The instrument validity test uses the Pearson Product Moment formula and the reliability test uses the Alpha-Cronbach formula. The hypothesis test in this study uses the T-test test. Based on the study's results, the Project Based Learning Model can be described effectively against technology-based geometry learning in elementary school students.